2003
DOI: 10.1207/s15327825mcs0603_2
|View full text |Cite
|
Sign up to set email alerts
|

Undermining Mothers: A Content Analysis of the Representation of Mothers in Magazines

Abstract: Mother wars, the pitting of at-home and employed mothers against each other, dominate public discourse. Mother roles are contested and, as a result, mothers are inundated with contradictory messages that affirm a particular mother role and simultaneously condemn a mother for achieving it. This content analysis explores 4 maternal contradictions in contemporary women 's magazines: (a) Buxton (1998) and Maushart (1999) contended that we are living in a historically and culturally unprecedented era of contested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In another study, we conducted a content analysis of double bind messages in women's magazines (Johnston & Swanson, 2003b). That study revealed that magazines promote particular ideals of motherhood and then condemn mothers for achieving the ideal.…”
mentioning
confidence: 99%
“…In another study, we conducted a content analysis of double bind messages in women's magazines (Johnston & Swanson, 2003b). That study revealed that magazines promote particular ideals of motherhood and then condemn mothers for achieving the ideal.…”
mentioning
confidence: 99%
“…Feminist media scholars have also examined how work and working are presented in women's magazines, including as a potential conflict with traditional notions of motherhood. In their discussion of the maternal contradictions that they found in women's magazines in the late 1990s, Johnston and Swanson (2003) noted the relative absence of working mothers, "who may be confident and successful, but the message is that there are not many mothers who can make this work" (p. 262).…”
Section: Reviewmentioning
confidence: 99%
“…The ensuing uproar led to French's resignation as creative director of wPP Group (Bosman, 2005). while French's original statements were rightly lambasted as sexist, his comments published in The Guardian are resonant with those of feminist researchers such as Deirdre Johnston and Debra Swanson (2003), who have observed, "Mothers live the double bind of professional woman versus good mother" (p. 244). In the controversial cover story of the July 2012 issue of The Atlantic, titled "why women Still Can't Have It All," Anne-Marie Slaughter noted that "to value family over professional advancement, even for a time-is directly at odds with the prevailing social pressures on career professionals."…”
mentioning
confidence: 99%
“…An online database search, using the term ''health'' in the search box, was used to locate articles. Full-length pieces, boxed highlights, or question and answer columns were included (Johnston & Swanson, 2003). Consistent with previous literature, articles were at least 75 words or longer (Pellechia, 1997).…”
Section: Samplementioning
confidence: 99%